Distribusi Musiman Nitrat dan Fosfat serta Pemodelan Klorofil-a sebagai Indikator Ekologis Keberlanjutan Budidaya Kappaphycus alvarezii di Pulau Tarakan - Cahyadi, Jimmy; Prayitno, Slamet Budi; Desrina, Desrina; Purwanti, Frida (Universitas Diponegoro, 2025)
Seaweed farming needs essential nutrients for growth. Nitrate and phosphate are essential nutrients for the growth of seaweed algae and phytoplankton produce chlorophyll-a. Chlorophyll-a content is needed in the photosynthesis process and triggers seaweed metabolism to absorb more nutrients. This study describes the relationship between nitrate, phosphate, chlorophyll-a for west and east monsoon waters with other water quality parameters in Tarakan Island. Insitu and exsitu measurements of water quality samples at 14 stations were determined by stratified random sampling in March 2024 for the west monsoon and June 2024 for the east monsoon. The distribution of chlorophyll-a was obtained from observations of the JAXA GCOM-C OCEAN CHLA V3 satellite image and the ocean contour model from BIG. There are significant differences in the distribution of chlorophyll-a, phosphate, and nitrate in the west and east monsoons. Chlorophyll-a distribution in the west monsoon of 0.60-1.10 mg/m3 tends to be higher than that in the east monsoon of 0.50-0.85 mg/m3 divergent pattern and correlates with nitrate, phosphate, water brightness, turbidity, sea surface temperature, current and pH. Water quality in the east and west monsoons supports seaweed farming. Budidaya rumput laut membutuhkan nutrien penting untuk pertumbuhannya. Nitrat dan fosfat merupakan nutrien penting untuk pertumbuhan algae rumput laut dan fitoplankton penghasil klorofil-a perairan. Kandungan klorofil-a dibutuhkan pada proses fotosintesis dan memicu metabolisme rumput laut menyerap lebih banyak nutrien. Penelitian ini menjelaskan keterkaitan nitrat, fosfat, klorofila-a perairan musim angin barat dan timur bersama parameter kualitas perairan lainnya di Pulau Tarakan. Pengukuran insitu dan exsitu pada 14 stasiun ditetapkan secara stratified random sampling bulan Maret 2024 mewakili musim angin barat dan Juni 2024 musim timur. Distribusi klorofil-a diperoleh dari pemantauan citra satelit JAXA GCOM-C OCEAN CHLA V3 dan pemodelan kontur laut dari BIG. Terdapat perbedaan signifikan distribusi klorofil-a, fosfat dan nitrat musim angin barat dan timur. Distribusi klorofil-a perairan musim barat 0,60-1,10 mg/m3 cenderung tinggi dibandingkan musim timur 0,50-0,85 mg/m3 berpola divergen dan berkorelasi dengan kadar nitrat, fosfat, kecerahan perairan, kekeruhan, suhu permukaan laut, arus dan pH. Kualitas perairan musim angin timur dan barat mendukung budidaya rumput laut.